Advances in the Application of Repetitive Transcranial Magnetic Stimulation for Acute and Maintenance Treatment of Major Depressive Disorder - LI Mingzhu; YAN Hao (Xiehe Yixue Zazhi)
Major depressive disorder (MDD) is a prevalent psychiatric condition characterized by high rates of prevalence and recurrence. Repetitive transcranial magnetic stimulation (rTMS) has been widely utilized in the acute phase treatment of MDD and has shown potential in maintenance therapy. However, the factors influencing the efficacy of rTMS during the acute phase and the sustainability of its long-term therapeutic effects remain incompletely understood. Additionally, a consensus on the optimal maintenance treatment protocol has yet to be established. This article reviews recent evidence on the application of rTMS in both acute and maintenance treatment of MDD, aiming to summarize current research progress and provide insights for the further promotion and application of rTMS in clinical practice.